(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Ekavimshatika Guggulu is mentioned in Bhavaprakasha Madhyamakhanda Kushta Adhyaya and Bala Taila mentioned in Bhela Samhita Vata Vyadhi Adhyaya. Most of the drugs in Ayurveda, a holistic medical science, emphasizes the importance of Prakriti, a unique concept that determines an individual’s physical, mental, and socio-behavioral health. Prakriti is determined at the time of fertilization by the dominance of Dosha in Shukra (sperm) and Shonita (ovum) and remains unchanged throughout life. Medha, or intellect, is another crucial concept in Ayurveda that encompasses both grasping power (Grahanshakti) and understanding (Dharanshakti). This study aimed to explore the relationship between Sharirika Prakriti and Medha by analysing classical Ayurvedic literature, dictionaries, and research publications, as well as comparing the concept of Medha with the modern psychological concept of intelligence quotient (IQ). The analysis reveals that Vata Prakriti individuals have good short-term memory but poor long-term memory, while Pitta Prakriti individuals are intelligent and dominate conversations. Kapha Prakriti individuals exhibit self-control, strong faith in Sastras, and exceptional memory, although they take longer to grasp the subjects. The seat of the Medha is inferred to be the Hridaya (heart), as it is the location of Sadhaka Pitta, which is responsible for the manifestation of Medha. This study highlights the potential of integrating traditional Ayurvedic wisdom with contemporary psychological assessments to develop a more comprehensive understanding of human intelligence and cognitive functioning.